Exploring The Relevance Of Pantheism With The Halaika Beliefs Of The Inner Boti Tribe - Yohanis Pandie, Remegises Danial (Jurnal Sosiologi Agama, 2025)
This article is a development of the Simlitabmas research grant from the Indonesian Ministry of Education and Culture that I did in 2022 in Boti Village, Ki’e District, South Central Timor Regency and has been published in book form and as my thesis during college. The research that I raised at that time was the Cultural Feudalism of the Boti Tribe According to the Perspective of Paulo Freire’s Theory of Liberating Education and Its Implementation in Christian Religious Education. In developing this article, I focus on the essence of halaika through the sociology of religion in order to find its scientific concept and see its relevance to pantheism. The Qualitative Ethnographic Method was used to see the cultural side and the halaika belief side of the Boti Dalam tribe. Literature study was used to add to the literature review related to pantheism. The results of the study show that both have relevance in terms of the meaning of nature as a source of life for humans. Where, nature is a place for humans to live and maintain their lives. In addition, both also believe that behind the existence of nature and human life there is something that envelops them in the limitations of their understanding regarding things that they cannot do. Nature also provides an understanding that what is visible is God who is in the invisible, so that the existence of nature and God becomes an inseparable unity for both.